2018
DOI: 10.4314/rejhs.v5i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vigabatrin, carbamazepine or its combination on the pituitarygonadal axis in male Wistar rats

Abstract: Objectives: Epilepsy is the most common non-infectious neurologic disease in developing African countries following stroke and Alzheimer's disease. Most conventional antiepileptic drugs, due to their centrally acting potentials have been implicated in the deregulation of reproductive hormones. This study assessed the effect of the single and combined administration of vigabatrin (VIG) and carbamazepine (CBZ) on the pituitary-gonadal axis of male Wistar rats.Methods: Fifty male Wistar rats were randomly divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
(18 reference statements)
2
6
1
Order By: Relevance
“…This finding is in contrast to the report of Akinsomisoye et al. (2017), that carbamazepine–vigabatrin adjunctive treatment had no significant effect on the testicular weight of Wistar rats. The variation in this study relative to Akinsomisoye and co‐worker's report may be dependent on the mechanism of action of the AEDs (carbamazepine–vigabatrin adjunctive treatment).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is in contrast to the report of Akinsomisoye et al. (2017), that carbamazepine–vigabatrin adjunctive treatment had no significant effect on the testicular weight of Wistar rats. The variation in this study relative to Akinsomisoye and co‐worker's report may be dependent on the mechanism of action of the AEDs (carbamazepine–vigabatrin adjunctive treatment).…”
Section: Discussioncontrasting
confidence: 99%
“…Sperm viability study was done according to the method of Akinsomisoye et al. (2017). Briefly uniform spermatozoa smear was done on slides with eosin/nigrosin stain.…”
Section: Experimental Designmentioning
confidence: 99%
“…It is well known that sperm count is the cumulative result of all phases of spermatogenesis and is one of the most sensitive tests for evaluating the infertility status of animals. 51 In addition, normal sperm motility plays a vital role in sperm fertilizing capability. 52 Ketamine-induced apoptosis, hormonal changes, and increased lipid peroxidation collectively adversely affected the process of spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the involvement of many antiepileptic drugs in the induction of nervous and endocrine derangements (Falokun et al., 2010; Lee, 2014; Olaibi et al., 2014), with consequential effects on reproductive function (Akinsomisoye et al., 2017; Wisniewski et al., 2015). Additionally, carbamazepine has been reportedly implicated as liver enzyme‐inducing drugs, thereby increasing serum sex hormone‐binding globulin (Verrotti et al., 2011), and thus diminished bioactivity of testosterone (Keerthy et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, prolonged AED administration is reportedly associated with a diverse adverse effect such as behavioural/psychiatric disorders (Lee, 2019), metabolic disruption (St Louis, 2009), hepatotoxicity (Ayalew & Muche, 2018), and alterations in bone turnover markers (Arora et al., 2016) to mention but a few. Moreover, sexual dysfunction and reproductive disorders are more common among patients with epilepsy than any typical population (Atif et al., 2016; Isojärvi, 2008; Luef, 2010; Wu et al., 2018), while there are consistent pieces of evidence on the adverse effect of some AEDs particularly on the testicular dysfunction (Akinsomisoye et al., 2017; Osuntokun et al., 2017), deregulation of sex hormones (Herzog et al., 2017), reproductive toxicity (Bairy et al., 2010; Karaduman et al., 2019), and reduction of seminal quality (Falokun et al., 2010).…”
Section: Introductionmentioning
confidence: 99%